Photocatalytic H2 Evolution Integrated with Selective Oxidation of Furfuryl Alcohol to Furfural Promoted by NiMoS4/Zn0.6Cd0.4S Nanocomposite - Yang, Jinbo; Lin, Shengqi; Li, Chunhe; Ren, Kuankuan; Ye, Qiufeng; Dou, Weidong (Energy & fuels, 2024)
Utilizing photocatalytic technology to efficiently convert biomass-derived compounds into value-added chemicals and release hydrogen gas can effectively address energy and environmental issues. For this purpose, we fabricated a series of NiMoS4/Zn0.6Cd0.4S nanocomposites through a simple two-pot hydrothermal treatment. Dexterously, the photoexcited electrons and holes can be simultaneously utilized to participate in a photocatalytic redox reaction, effectively achieving the oxidation of furfuryl alcohol while cooperating with H2 evolution. The hydrogen evolution rate of 10%-NiMoS4/Zn0.6Cd0.4S nanocomposite in 1.50 vol % furfuryl alcohol aqueous solution is as high as 289.5 μmol·h–1, which is approximately 2895 and 41 times higher than that of pure NiMoS4 and Zn0.6Cd0.4S, respectively. Meanwhile, after 13 cycles of photocatalytic reaction, the conversion efficiency and selectivity of converting furfuryl alcohol to furfural are 68.5% and 94.0%, respectively. This photocatalyst also shows high photocurrent, low impedance, and efficient photogenerated carrier separation and transport properties, which can be attributed to the establishment of an ohmic junction between NiMoS4 and Zn0.6Cd0.4S. It is anticipated that this work can provide inspiration for the effective conversion of biomass-derived platform chemicals into high-value chemicals through visible-light-driven photocatalytic technology.